Improving knowledge discovery through the integration of data mining techniques - Usman, Muhammad (Information Science Reference, an imprint of IGI Global, 2015)
"This book provides insight concerning the integration of data mining and data warehousing for enhancing the knowledge discovery process" - Provided by publisher
Includes bibliographical references and index
Keywords: Knowledge management; Data mining